About procedural guarantees and judicial activism: What kind of labor judges do we have? - Vásquez Rosales, Karol (2021)
In this paper, we examine some perspectives on the procedural doctrines of procedural guarantee and judicial activism, from which we extract their postulates, characteristics, and manifestations, in order to then analyze what type of labor judges we have. For this purpose, we will use as our methodology the documentary review of the recent doctrinal analyses carried out a decade after the enactment of the New Labor Procedure Law (NLPT hereinafter), the «good practices» implemented by the labor judges of our country, the Performance Protocol for Labor Hearings elaborated by the Institutional Technical Team for the Implementation of the New Labor Procedure Law (ETII hereinafter), the Protocol for Virtual Judicial Hearings and the Diagnosis of Capacities of Judges who apply the NLPT, from which, after the pertinent discussion, we will conclude that we have predominantly activist labor judges.